The effectiveness of PCR-RT method for etiological diagnosis of atypical forms of whooping cough - A. Yu. Medkova; E. G. Syomin; L. N. Sinyashina; I. V. Babachenko; G. I. Karataev (LLC "Diagnostics and Vaccines", 2022)
The aim of the study was to evaluate the effectiveness of the PCR-RТ method using the PCR-RТ-IS test system for the etiological diagnosis of whooping cough in the examination of patients with infectious respiratory pathology with prolonged cough and in contact persons. 113 children aged from 1 month to 17 years, 11 months and 29 days, and 146 contact family members were examined. Regardless of the initial diagnosis, all children were examined for whooping cough by bacteriological, molecular genetic and serological methods. For molecular genetic diagnostics a commercial kit and PCR-RT-IS test-system developed at the Gamaleya Research Center were used. The contact persons were examined by the bacteriological method and using the PCR-RT-IS test-system. During the initial examination the diagnoses «Acute respiratory viral infectious», «Acute rhinopharyngitis», «Acute laryngotracheitis», «Acute bronchitis», «Pneumonia» were established. The severity of cough in contact persons was different - from a typical spastic «whooping cough» to complete absence of cough. By using the PCR-RT-IS test-system we developed, the DNA of pertussis pathogen was detected in groups of patients with «Acute rhinopharyngitis» in 34.4% of cases, «Acute laryngotracheitis» - in 64.3%, «Acute bronchitis» - in 69%, with a diagnosis of «Pneumonia» - in 33.3% of cases. In a number of cases combined course of whooping cough with respiratory infections (respiratory syncytial virus, rhinovirus and others) was detected. In the examined contact persons the causative agent of pertussis was detected using the PCR-RT-IS test-system in 51,4% of cases.